13(t-4)+5t=6(3t+3)-10

Simple and best practice solution for 13(t-4)+5t=6(3t+3)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(t-4)+5t=6(3t+3)-10 equation:


Simplifying
13(t + -4) + 5t = 6(3t + 3) + -10

Reorder the terms:
13(-4 + t) + 5t = 6(3t + 3) + -10
(-4 * 13 + t * 13) + 5t = 6(3t + 3) + -10
(-52 + 13t) + 5t = 6(3t + 3) + -10

Combine like terms: 13t + 5t = 18t
-52 + 18t = 6(3t + 3) + -10

Reorder the terms:
-52 + 18t = 6(3 + 3t) + -10
-52 + 18t = (3 * 6 + 3t * 6) + -10
-52 + 18t = (18 + 18t) + -10

Reorder the terms:
-52 + 18t = 18 + -10 + 18t

Combine like terms: 18 + -10 = 8
-52 + 18t = 8 + 18t

Add '-18t' to each side of the equation.
-52 + 18t + -18t = 8 + 18t + -18t

Combine like terms: 18t + -18t = 0
-52 + 0 = 8 + 18t + -18t
-52 = 8 + 18t + -18t

Combine like terms: 18t + -18t = 0
-52 = 8 + 0
-52 = 8

Solving
-52 = 8

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3(5+8n)=15+6n | | (3-w)(4w+2)=0 | | -(7y+2)-(-6y-7)=3 | | 10=y-13 | | 10(-p-2)+9(3p-5)= | | 4.5a+.5=18 | | 4.5a+.5=8 | | 8n+2-4n=-9-7n | | x-7.2=-6.5 | | (5x-1)/4=x+6 | | s+28=23 | | -102=-6(3+7x) | | (3x-2)/4=7 | | p-4p=24 | | -6(5+3n)=114 | | x-3x+5=12 | | X-2-3=2X-7 | | 3X-2-3=2X-7 | | -2(4-8n)=120 | | 3X-2X-3X=2X-7X | | -21=9k-2k | | 360-(5x+90)= | | 85=-5(-5-2v) | | 2(4-4x)=21+14x | | 2+5(5p+6)=232 | | 12+19x+4x^2=0 | | -6(3n+5)+5=-151 | | 5v^2-90=0 | | 2(3w-8)*(2w)=40 | | 6+2(y-4)=13 | | 2+22= | | 7.11=2(3.14)R |

Equations solver categories